Climate security in the digital public square: A lookback at the conversations of 2022 and the road to COP 28 - Silveira Carneiro, Bia; Tucci, Giulia; Taiwo, Ibukun (2023)
Innovative research methodologies have demonstrated that social media platforms can serve as proxies for public discourse and engagement, yielding invaluable insights into our society’s collective consciousness. The platform X (formerly known as Twitter) has historically been popularly referred to as a digital public square, with daily, rapid-fire conversations on topical issues. Thus, it provides a wealth of data and rich insights into the public sentiment about important topics.